Penggunaan LKPD Berbasis Pendekatan Matematika Realistik untuk Meningkatkan Kemampuan Penalaran Matematis Siswa SMP - Adila Nazwani, Siti Nur; Sabaruddin, Sabaruddin; Husna, Raudatul; Anggreni, Fenny (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to examine the use of Student Worksheets (LKPD) designed based on the Realistic Mathematics Education (PMR) approach in improving the mathematical reasoning skills of junior high school students. The background of this study is the low achievement of Indonesian students in various national and international assessments, such as PISA. The method used is a quasi-experimental with a One Group Pretest-Posttest design. The research sample was taken purposively from grade VIII students at SMP Negeri 3 Langsa in the 2025/2026 academic year. The instrument used was an essay test developed in accordance with the mathematical reasoning indicators from NCTM and has gone through a validation process. Data analysis was carried out descriptively and inferentially using the Paired Sample t-Test. The results showed a significant increase in scores between the pretest and posttest, where the average score increased from 62 to 75 with a significance value of p = 0.000 (<0.05). These findings prove that LKPD based on the RME approach is effective in improving students' mathematical reasoning skills. Therefore, a contextual learning approach such as PMR is important to apply in teaching mathematics at the junior high school level. Keywords: LKPD, Mathematical Reasoning PMR, Pretest-Posttes